The Effectiveness of Nominal, Delphi, and Interacting Group Decision Making Processes - Ven, Andrew H. Van de; Delbecq, André L. (Academy of Management Journal, 1974)
The conventional interacting group is compared with nominal and delphi groups in terms of the quantity of ideas generated and perceived satisfaction of participants. On an applied fact-finding problem with no known solution, the nominal and delphi groups are equally effective and both clearly are more effective than conventional interacting groups.